Construction technology critical concepts in construction - Chinowsky, Paul (Critical concepts in construction, 2014)
The collection is introduced by the Editor to provide the context of the industry as a basis for Construction Technology emergence and each volume has its own short introduction. These volumes present a comprehensive review of the role of technology in responding to the continuous changing environment of the construction industry